A qualitative study of how COVID-19 impacts on Australians' hopes and dreams - Quincy F. Huang; Floraidh Rolf; Lauren A. Booker; Taleah Moore; Sandra C. Thompson (BMC, 2022)
Abstract Background Although beginning in 2019, it was early in 2020 that the global community began to comprehend the significant impact that a pandemic of a new coronavirus might have on their own lives. This study was undertaken 6-9 months after significant public health restrictions were introduced within Australia and examined the impact of the COVID-19 on individuals' hopes and dreams for their future. Methods Community members who responded to a survey about COVID-19 were invited to participate in follow up interviews if they reported living with a chronic condition. Participants across Australia who consented were interviewed between August and December in 2020 over telephone or videoconferencing. A specific question was included regarding the impact of COVID-19 on their hopes and dreams for the future. Rapid identification of themes with an audio recordings technique was used to generate themes from the data. Results The 90 participants were predominantly female (77%) and ranged in age from 20 to 81 years with a mean age of 50 years and lived in several Australian states. Following immersive analysis of interviews, the identified common themes impacting people's hopes and dreams revealed: concerns for their own and others' job stability and future work; the impact on travel both for holidays, business and reconnecting with family; reassessing of personal and social values; and the intergenerational impact of such a profound pandemic, with concern for younger people particularly prominent in those concerns. Participants reflected on their loss of future dreams, with possibilities they had planned and worked towards not possible in the short term. Conclusions The responses provide a window into how people view their future goals and aspirations during a time of global and local instability and highlights the potential future impacts of the COVID-19 pandemic.